Excluding the Jews: The Aryanization of Danish-German Trade and German Anti- Jewish Policy in Denmark 1937-1943 - Jacob Halvas Bjerre (Copenhagen Business School (CBS), 2018)
The purpose of this dissertation is to explore and analyze the German Judenpolitik in Denmark by focusing on the Aryanization of Danish-German trade relations and anti-Jewish policies in Denmark from 1937 until August 1943. As a second research goal, it examines the reactions of the Danish government to the German Judenpolitik. These goals have been developed into four research questions: 1. How was Germany's ambition to Aryanize its foreign trade developed into concrete policies, and how were these policies implemented into Danish-German trade relations as part of the German Judenpolitik in Denmark? 2. How did the German legation assist in formulating and executing the German Judenpolitik in Denmark? 3. How did the Danish government respond to the German Judenpolitik? 4. Based on the model Stages of Persecution, which stages and forms of Judenpolitik can be identified in Denmark during 1937-August 1943? These are answered by using qualitative and primary historical sources. I therefore apply a historical method which is combined with a four tier analytical approach. The overarching one is Peter Longerich's definition of Judenpolitik understood as a tool to describe and analyze the complex processes of German anti-Jewish policy and politics. This analytical and thematical concept is applied to the Danish-German relationship in the period from 1937 to August 1943.
hdl:10398/9692
Keywords: 650